Cryptococcus gattii in the Age of Whole-Genome Sequencing - Wieland Meyer (American Society for Microbiology, 2015)
ABSTRACT Cryptococcus gattii, the sister species of Cryptococcus neoformans, is an emerging pathogen which gained importance in connection with the ongoing cryptococcosis outbreak on Vancouver Island. Many molecular studies have divided this species into for major lineages: VGI, VGII, VGIII, and VGIV. This commentary summarizes the whole-genome sequencing (WGS) studies that have been carried out with this species, re-emphasizing the phylogenetic relationships, showing chromosomal rearrangements between those four groups, and identifying VGII as ancestral population within C. gattii. In addition, WGS specific to VGII, containing the Vancouver Island outbreak genotypes and those from the Pacific Northwest region of the United States, has placed the origin of this lineage within South America and identified specific genes responsible for either brain or lung infection. It also showed, that many genotypes are spread across a number of different continents, as has been previously shown by multilocus sequence typing (MLST). In addition, it showed that recombination occurs more frequently between mitochondrial than nuclear genomes.